NUF2 is a valuable prognostic biomarker to predict early recurrence of hepatocellular carcinoma after surgical resection. Issue 3 (4th February 2019) - Wang, Yu; Tan, Peng Yang; Handoko, Yohana Ayupriyanti; Sekar, Karthik; Shi, Ming; Xie, Chan; Jiang, Xiao‐Dan; Dong, Qing‐Zhe; Goh, Brian Kim Poh; Ooi, London Lucien; Gao, Zhiliang; Hui, Kam Man
Abstract : Early tumor recurrence after curative surgical resection poses a great challenge to the clinical management of hepatocellular carcinoma (HCC). We conducted whole genome expression microarrays on 64 primary HCC tumors with clinically defined recurrence status and cross‐referenced with RNA‐seq data from 18 HCC tumors in the Cancer Genome Atlas project. We identified a 77‐gene signature, which is significantly associated with early recurrent (ER) HCC tumors. This ER‐associated signature shows significant enrichment in genes involved in cell cycle pathway. We performed receiver operating characteristic (ROC) analysis to evaluate the prognostic biomarker potential of these 77 genes and Pearson correlation analysis to identify 11 close clusters. The one gene with the best area under the ROC curve in each of the 11 clusters was selected for validation using reverse‐transcription quantitative PCR in an independent cohort of 24 HCC tumors. NUF2 was identified to be the minimal biomarker sufficient to discriminate ER tumors from LR tumors. NUF2 in combination with liver cirrhosis could significantly improve the detection of ER tumors with an AUROC of 0.82 and 0.85 in the test and validation cohort, respectively. In conclusion, NUF2 in combination with liver cirrhosis is a promising prognostic biomarker for early HCC recurrence. Abstract : What's new? More than 60% of hepatocellular carcinomas (HCC) will recur after surgical resection. Patients who suffer early recurrence have a poorer prognosis than those whose tumors recur later. New biomarkers for early HCC recurrence are thus urgently needed. In this study, the authors found that the combination of liver cirrhosis plus increased expression of a single gene, NUF2, can predict early recurrence. NUF2 is thus a promising, novel prognostic biomarker that may improve the clinical management of HCC after curative resection.